Developing an integrated platform to enable hardware-in-the-loop for synchronous VR, traffic simulation and sensor interactions. (January 2022) - Ergan, Semiha; Zou, Zhengbo; Bernardes, Suzana Duran; Zuo, Fan; Ozbay, Kaan
Abstract: Hardware-in-the-loop (HIL) is a testing paradigm where physical sensors (e.g., monitoring sensors such as cameras and proximity sensors, and alarm sensors such as screaming traffic cones) are connected to a virtual test system that simulates reality (e.g., virtual work zone with simulated dangerous situations). This paradigm is well-suited for conducting user studies for work zone safety because virtual test systems can be implemented using virtual reality (VR), which allows for safe and realistic testing of a sensing system without putting workers in danger along with avoiding high upfront costs needed to generate physical research testbeds. However, when recreating physical work zones in VR, researchers face various challenges while representing traffic patterns in VR, such as the lack of bi-directional communication between traffic simulation platforms and user behaviors in VR, hardware compatibility and integration issues, and customization inflexibility during implementation. Researchers, who need to develop such platforms for research studies that involve high-risk exposure to participants, are in need of evaluating the options available for bringing together the components of such platforms. This study provides an overview of alternative ways to integrate components of platforms that enable hardware-in-the-loop for synchronous VR, traffic simulation, and sensor interactions to position researchers to make decisions based on the pros and cons of each alternative. This paper also presents the implementation of such an integrated platform that allows a two-way interface between traffic simulation and VR environments for work zone safety analysis. Outcomes of this work will lay out the steps in implementing the integrated and immersive platform to be used in work zone safety studies based on the guidance presented.